BEHAVIOURAL ANALYSIS IN THE VILLAGE FUND SYSTEM USING THE UTAUT METHOD - Fuad, Khoirul; Nurrokhmahwati, Nurrokhmahwati; Handayani, Retno Tri (IJIBE (International Journal of Islamic Business Ethics), 2021)
The information system aims to simplify, accelerate, and be responsible. The behavior in the use of technology is an essential part of achieving good village financial management using the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. The population of this research is all village government offices in Tegal Regency. This research is a quantitative study with primary data and a convenience sampling method. This research sample is village apparatus that is directly related to the village fund system (SISKEUDES). Meanwhile, the data analysis of this study uses SPSS software. The test results show that performance expectations negatively affect business expectations, social influences, and conditions that facilitate a positive and significant impact.